A review of South Korean Alloplasta Förster (Hymenoptera: Ichneumonidae: Banchinae) with description of a new species - Kang, Gyu-Won; Kolarov, Janko; Lee, Jong-Wook (Zootaxa, 2020)
South Korean Alloplasta species were examined in this study. Prior to this study, only A. longipetiolaris of this genus was previously known from South Korea. Four species are new records, A. kuslitzky, A. nigripes, A. maruyamana and A. subgrisea, and A. brevipetiolaris sp. nov. is described as new to science. Furthermore males of two species, A. kuslitzky and A. subgrisea, are described for the first time. An illustrated identification key is provided for the Alloplasta species known from South Korea.